Image analysis of plasmonic sensor for high-throughput biomarker detection - Li, Xiaochao. (2013)
In this project, we develop an image analysis algorithm to work with a surface plasmon resonance (SPR) biosensor for multiple bio-molecular interactions detection. The SPR biosensor measures the color change produced by surface plasmon excitation in the spectral domain. When bio-molecular interaction occurs at the sensor surface (such as antibody-antigen interaction), the refractive index value is varied and corresponding spectral shift will be produced in the spectrum.